The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.54987/jobimb.v6i1.386
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Aspergillus Species and Aflatoxin in Groundnut Sold in Gombe Metropolis

Abstract: The production of groundnut is constrained by several factors, among which is the contamination with Aspergillus sp. In addition to causing quantitative losses, some of the Aspergillus sp. produce highly toxic and carcinogenic chemical substances known as aflatoxins. Aflatoxin contamination of groundnut has gained global significance due to deleterious effects the contaminant has on human and animal health. This study aimed at investigating the occurrence of Aspergillus sp. in different groundnut samples as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This result indicates variation in amylase production among different strains of A. niger [21,25,26]. It was reported that A. niger isolated from soil have higher amylase production on different agricultural residues [8,15,24,[27][28][29]…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates variation in amylase production among different strains of A. niger [21,25,26]. It was reported that A. niger isolated from soil have higher amylase production on different agricultural residues [8,15,24,[27][28][29]…”
Section: Discussionmentioning
confidence: 99%